Strengthening Heritage-Based MSE Products in Supporting the Potential of Sangiran Tourism Village - Ismoyowati, Dewi; Mafruhah, Izza; Istiqomah, Nurul; Garvitiani, Evi; Suryanto, Suryanto (Journal of Innovation and Community Engagement, 2025)
Sangiran Tourism Village is administratively located in Krikilan Village, Kalijambe District, Sragen Regency. The location selection is purposive because Sangiran Tourism Village is located in Sragen Regency and has abundant potential in the form of heritage and ecology tourism. Another thing that supports the choice of location is that Sangiran Tourism Village is located in the Sangiran Ancient Human Site tourist complex, which is an international-class tourism resort and has been designated as a cultural heritage site by UNESCO. It is supposed that the tourism and creative industry potential in Sangiran Tourism Village can be developed further. In that case, it is expected that it will be able to improve the welfare and economy of the community, especially in Krikilan Village. The main problems in the Sangiran tourism village community are: a) There needs to be an introduction to science and technology related to the procurement of souvenirs that can be the mainstay of the region. b) There is no science and technology related to making souvenir designs that can arouse their creativity c) Types of souvenirs that are not in demand by visitors and relatively expensive in prices d) Marketing that still needs to be more extensive to increase sellers’ income. This triggered the service team to analyze the situation faced by the Sangiran community so as to find a point of discovery to hold training and assistance in making souvenirs. Community service in the context of community empowerment in Sangiran Tourism Village was carried out with the following objectives: a) Providing insight into souvenirs, including making models, b) introducing and providing training on designing alternative souvenirs, especially those that are typical of the Sangiran area. c) Assisting in making designs and models d) Assisting in the marketing of souvenirs that have been successfully produced.